Surveillance Rate and its Impact on Survival of Hepatocellular Carcinoma Patients in South Korea: A Cohort Study - Im, Sanghyuk; Jang, Eun Sun; Lee, Ju Hyun; Lee, Chung Seop; Kim, Beom Hee; Chung, Jung Wha; Kim, Jin-Wook; Jeong, Sook-Hyang (Cancer research and treatment, 2019)
Though regular surveillance of hepatocellular carcinoma (HCC) for high-risk patients is widely recommended, its rate and effectiveness are not clear. The aim of this study is to investigate the actual rate of HCC surveillance and its related factors and to clarify its impact on survival in a Korean HCC cohort. From 2012 to 2015, 319 newly diagnosed HCC patients were prospectively enrolled at a tertiary hospital. Patient interviews based on a structured questionnaire survey were conducted. Surveillance was defined as liver imaging test ≥ 2 times with at least 3-month interval within 2 years prior to HCC diagnosis. Surveillance rate was 39.8%. Of the HCC patients with high-risk factors, only 182 (57.1%) had knowledge for the need for regular surveillance, and 141 (44.2%) had the accurate information about the method (ultrasound-based study). Surveillance group showed a higher proportion of early HCC (p < 0.001) and a longer overall survival (p < 0.001) compared to non-surveillance group. The multivariable Cox regression analysis indicated Child-Pugh class A, history of anti-viral therapy, low serum α-fetoprotein level, non-advanced Barcelona Clinic Liver Cancer stage as independent predictors of overall survival, while regular surveillance was not (p=0.436). Less than half of the newly diagnosed Korean HCC patients were under surveillance and the accurate perception for the need of HCC surveillance was insufficient. Of those under surveillance, most patients were diagnosed with early stage HCC, which led to the improved survival. Comprehensive efforts to optimize the surveillance program for the target population are warranted.